What antiepileptic drugs are most effective? The results of the new Cochrane systematic review are published - Bezsheiko, Vitaliy (Psychosomatic Medicine and General Practice, 2017)
According to the results of the new Cochrane systematic review, carbamazepine and lamotrigine are most effective in partial, and sodium valproate - generalized epileptic seizures.